The Intention To Obtain Chartered Accountant: A Theory of Planned Behavior and Motivation Theory Approach - Sugeng Riadi (AKUNTANSI DEWANTARA, 2020)
This research aims to analyse the influence of attitudes, subjective norms, perceived behaviour control, comprehension, career motivation, economic motivation and achievement motivation on student’s intention to obtain the Chartered Accountant (CA). The data analysis technique used in this research is descriptive statistical analysis and hypothesis testing using multiple regression analysis. The results of this study prove that attitudes, career motivation and achievement motivation had a positive and significant on student intention to obtain the Chartered Accountant. While subjective norms, comprehension, perceived behaviour control and economic motivation has a negative and insignificant on student’s intention to obtain the Chartered Accountant.